Toxic elements in soil and rice in Ecuador - Atiaga, Oliva (2021)
The concentration of trace toxic metals (Cr, Zn, As, Pb, Cd, Cu, and Ni) in soil and rice plants, including the stems, leaves, and grain, from the main rice-producing provinces in Ecuador, was determined. Additionally, the soils were analyzed to determine their properties, composition, total content, bioavailable fraction, and geochemical fractions of toxic elements. Approximately 30% of soil samples in the case of Cr and Cu and 10% of samples in the case of Ni exceeded the legal thresholds for Ecuador. Moreover, for Cr and Cu, approximately 4% and 13% of samples, respectively, exceeded the threshold value of 100 mg kg−1 proposed for these two elements in several international regulations. Concentrations of As, Pb, and Cd in the soils were below the threshold values established both by Ecuadorian laws and by other countries. The concentrations of metals in rice plants did not correlate linearly with the total metal concentrations in the soil, nor with their bioavailability. However, the bioconcentration factors for As, Cd, Cu, Ni, and Zn could be predicted from bioavailability by a power law with exponents ranging from −0.724 to −1.625, which is typical of accumulator plants, where trace metal homeostasis plays an important role.